Primary Results from IMscin002: A Study to Evaluate Patient Preferences and Perceptions of Health Care Professionals for Atezolizumab Subcutaneous Versus Intravenous for the Treatment of NSCLC - Federico Cappuzzo, MD; Zanete Zvirbule, MD; Ernesto Korbenfeld, MD; Jaroslaw Kolb-Sielecki, MD; Dolores Isla, MD, PhD; Aleksandra Szczesna, MD, PhD; Amparo Yovanna Castro Sanchez, PhD; Alberto Bustillos, MD; Xiaoyan Liu, PhD; Fiona Young, MbChB; Nadia Tosti, PhD; Marta Freitas Monteiro, MSc, PhD; et al. (JTO Clinical and Research Reports)
Introduction: Subcutaneous (SC) atezolizumab, a co-formulation containing atezolizumab and recombinant human hyaluronidase PH20), has been approved for use in more than 50 countries for the same indications as intravenous (IV) atezolizumab. IMscin002 (NCT05171777), a phase 2, randomized, open-label, crossover trial, investigated patient preferences and health care professionals’ (HCPs’) perceptions of atezolizumab SC versus IV for the treatment of NSCLC; we report the primary results of IMscin002. Methods: Patients with programmed death-ligand 1-positive resected NSCLC who had completed adjuvant chemotherapy without evidence of recurrence, and chemotherapy-naive patients with programmed death-ligand 1–high metastatic NSCLC were randomized 1:1 to arm A (atezolizumab SC then atezolizumab IV) or arm B (atezolizumab IV then atezolizumab SC). After cycle 3, patients switched administration routes. After cycle 6, the patients chose the route of administration for the continuation period. The primary end point was patient preference for SC or IV atezolizumab, and the secondary end points were patient- and HCP-reported outcomes and safety. Results: A total of 179 patients were included in this study. Most patients (70.7%; n = 87 of 123) preferred SC atezolizumab over IV, with 79.4% (n = 85 of 107) choosing SC atezolizumab during the continuation period. Among the HCPs, 75.2% (n = 76 of 101) indicated that atezolizumab SC was more convenient than IV, and 77.8% (n = 77 of 99) strongly agreed or agreed that it would allow patients to spend less time in care units. No new or unexpected safety findings were identified, and switching between administration routes was well tolerated and managed. Conclusions: Most patients preferred SC atezolizumab over IV. There were no new safety findings, and switching between the administration routes was well tolerated. These results support the preference for SC formulations to reduce the treatment burden.